Narrativas sobre el pasado antiguo en textos escolares del Perú - Accinelli Obando, Aldo Javier (Pontificia Universidad Católica del Perú, 2025)
This paper studies how the ancient past has been constructed in textbooks meant for high school freshmen in Peru. Seven different texts published from 1943 to 2015 have been analysed comparatively, in order to discover patterns for understanding the narrative schemes of these books. The research is based on questions about who is represented and in which manner; what kind of source is used, and what are the objectives of the text. Finally, the construction of the ancient past is delineated, and the consequences of these narrative schemes are discussed.

Mediante el análisis comparativo de siete libros de texto publicados entre 1943 y 2015, se estudian relatos sobre el pasado lejano orientados a alumnos del primer año de secundaria del Perú. Se identifican los patrones sobre la información presentada que permiten comprender los esquemas narrativos de estos libros. La investigación se articula en torno a quiénes son representados y cómo, además de qué tipo de fuente se usa y cuáles son los objetivos del texto. Finalmente, se delinea la construcción del pasado antiguo y se discuten las consecuencias de estos esquemas narrativos.
Narratives about the ancient past in Peruvian textbooks, 1943-2015: Between evolutionism and nationalism
Keywords: Ancient Peru; Textbooks; Education; 20th century; 21st century; Perú antiguo; Libros de texto; Educación; Siglo XX; Siglo XXI; https://purl.org/pe-repo/ocde/ford#6.00.00